RETRACTED: Joint cultivation of sturgeon and tilapia in cages on small rivers (Krasnodar territory) - Abramchuk Alexey; Moskul Georgy; Pashinova Natalya (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001